Book reviews - Rączkiewicz, Małgorzata; Pierzgalski, Michał (International Studies. Interdisciplinary Political and Cultural Journal, 2011)
Z. Brzezinski, B. Scowcroft, America and the World: Conversations on the Future of American Foreign Policy, Basic Books, New York 2008 Jeff Gill, Essential Mathematics for Political and Social Research, Cambridge University Press, New York 2006, pp. 448.